Prognosis of advanced stage non-small-cell lung cancer patients receiving chemotherapy: adenocarcinoma versus squamous cell carcinoma (Medical Journal of Indonesia, 2020)
BACKGROUND In Indonesia, lung cancer is one of the most prevalent solid cancer with the highest mortality rate. However, studies to identify prognostic factors associated with mortality are lacking. Thus, this study was aimed to determine the association of histological subtypes and prognosis of advanced stage non-small-cell lung cancer (NSCLC) patients receiving chemotherapy. METHODS This study focused on a retrospective cohort consisting of 60 patients with advanced stage NSCLC and treated with chemotherapy. Patients with NSCLC stage IIIB or stage IV, age ≥18 years, and good performance status were recruited. The outcomes were one-year mortality and treatment response. Gender, age, body mass index, staging, and performance status were evaluated. Chi-square and Fisher’s exact tests were used. RESULTS Two common histological subtypes, adenocarcinoma (68.3%) and squamous cell carcinoma (31.7%), were observed among all subjects. Four patients (6.7%) died during one-year observation period. Mortality rate was higher in squamous cell carcinoma (10.5%) patients than in adenocarcinoma (4.9%). Underweight patients had higher risk of death (relative risk [RR] = 1.09, 95% confidence interval [CI] = 1.00–1.19) and disease progression (RR = 1.30, 95% CI = 1.12–1.51). In adenocarcinoma, metastasis was a risk for progressive disease (RR = 1.35, 95% CI = 1.09–1.66). In squamous cell carcinoma, men had a lower risk of disease progression (RR = 0.11, 95% CI = 0.03–0.41). CONCLUSIONS Squamous cell carcinoma had comparable one-year mortality and disease progression rate with adenocarcinoma type in advanced stage NSCLC. However, underweight patients had a higher risk of mortality and disease progression.